BIR JINSLI EMAS DIELEKTRIK BILAN TO‘LDIRILGAN KONDENSATOR ELEKTR SIG‘IMINI HISOBLASH - Yavidov, B.; Ashirova, N.; Qalbaeva, H.; Sultanov, S. (SCIENCE and SOCIETY, 2018)
In the article the method of problem solution on calculation of electric capacity of capacitors is considered. In particular, calculation of electric capacity of plane, spherical and cylindrical capacitors are shown in case when an area between plates of capacitor filled with nonhomogeneous dielectric medium. It is assumed that dielectric permittivity of the dielectric medium, placed between capacitor’s plates, varies linearly with respect to the distance from one plate to another one. The method of problem solution considered in the article may be used on calculation of moments of inertia of heterogeneous bodies.